STRATEGI PROMOSI SENDRATARI SUGRIWA SUBALI OLEH PEMERINTAH KULON PROGO UNTUK MENARIK WISATAWAN - Gasa Ari Pamungkas; Winarto Winarto (Sekolah Vokasi Universitas Gadjah Mada, 2021)
This journal analyses the promotion strategy of Sugriwa Subali ballet by Kulon Progo government to attract tourists, starting from the production process to the performance. This is motivated by the several excellence programs made by Kulon Progo government to develop the Kulon. Information was obtained from field studies and literature reviews. While conducting a field study in Kulon Progo, the writer conducts an interview with the director of the Sugriwa Subali. The writer also took a note, recorded, documented, and obtained several related documents. The writer also conducts a literature review by reading journals and online articles. The data were presented in qualitative form has been compiled through observation. The results showed that the promotion used by the Kulon Progo government was assisted by the organizers of the Sugriwa Subali ballet by using media such as poster, brochures, online media, TV program and press conferences.